Evoked axonal oxytocin release in the central amygdala attenuates fear response - Knobloch-Bollmann, Hanna Sophie; Eliava, Marina; Khrulev, Sergey; Cetin, Ali Haydar; Seeburg, Peter H.; Grinevich, Valéry (Neuron, 2012)
Summary: The hypothalamic neuropeptide oxytocin (OT), which controls childbirth and lactation, receives increasing attention for its effects on social behaviors, but how it reaches central brain regions is still unclear. Here we gained by recombinant viruses selective genetic access to hypothalamic OT neurons to study their connectivity and control their activity by optogenetic means. We found axons of hypothalamic OT neurons in the majority of forebrain regions, including the central amygdala (CeA), a structure critically involved in OT-mediated fear suppression. In vitro, exposure to blue light of channelrhodopsin-2-expressing OT axons activated a local GABAergic circuit that inhibited neurons in the output region of the CeA. Remarkably, in vivo, local blue-light-induced endogenous OT release robustly decreased freezing responses in fear-conditioned rats. Our results thus show widespread central projections of hypothalamic OT neurons and demonstrate that OT release from local axonal endings can specifically control region-associated behaviors.